Mengembangkan Kemampuan Berfikir Kritis Melalui Metode Pembelajaran Improve - Mujib, Mujib (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
The focus of this research is to look at the development of students' critical mathematical thinking skills of IMPROVE learning methods. This research is quasi-experimental research with a population of a student of class VII SMP PGRI Kec. Sukarame Kota Bandar Lampung for the academic year 2015/2016, while the sample in this research is the students of class VII, which come from two classes in each class chosen at random. The instruments used in this study. Data analysis using a different test. Two-way ANOVA test and test. Based on the results of data analysis resulted in mathematical learning group of students who gain learning better than students who obtain conventional learning. Students who have received IMPROVE learning, upper category students have improved mathematical critical thinking skills than middle and lower category students, while improving students' mathematical thinking skills under category is better than middle category students. There is an interaction between the learning factors with the category of students' ability there is an increase in critical thinking skills mathematically.